Aplikasi Pengelolaan Persediaan Bahan Pada Usaha Kecil Menengah Pakaian Jadi - Antonius Susanto; Cecilia Esti Nugraheni; Maria Widyarini (Jurnal Teknik Informatika dan Sistem Informasi, 2021)
Clothing is one of the basic or primary needs. With the influence of clothing fashion that continues to grow, many Small and Medium Enterprises (SMEs) have sprung up engaged in the clothing sector. SMEs are one of the driving forces of the Indonesian economy. SMEs engaged in the clothing sector are businesses that produce apparel. The materials used in the manufacture of clothing also vary, so that inventory management and material requirements planning are essential processes in the manufacture of clothing. In this study, a simple mobile application was developed that can be used for material inventory management for SMEs. The primary function of this application is to record materials (inventory) and plan production needs using the Reorder Point (ROP) method. The Reorder Point (ROP) method is an order limit point helpful in knowing when a company holds an order. Program development using Android Studio IDE with Flutter framework and Dart programminglanguage. The results of functional testing on this application are 90% achieved following the expected results. The user acceptance test concludes that this application has the potential to facilitate SMEs in managing the inventory of material.